2016
DOI: 10.1371/journal.pone.0162918
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Characterizing the Human Nasal Cycle

Abstract: Nasal airflow is greater in one nostril than in the other because of transient asymmetric nasal passage obstruction by erectile tissue. The extent of obstruction alternates across nostrils with periodicity referred to as the nasal cycle. The nasal cycle is related to autonomic arousal and is indicative of asymmetry in brain function. Moreover, alterations in nasal cycle periodicity have been linked to various diseases. There is therefore need for a tool allowing continuous accurate measurement and recording of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 89 publications
(88 reference statements)
1
62
0
1
Order By: Relevance
“…The nasal cycle is a normal ultradian physiological phenomenon that manifests in all mammals, 52 where each nasal airway takes turns at conducting a greater apportionment of tidal airflow. The status of airflow dominance between the right and left nasal airways is correlated with sympathetic and parasympathetic dominant states, respectively, as regulated by the ANS, 53,54 the lateralised ultradian rhythm of alternating cerebral hemispheric dominance 55,56 and is tightly coupled to sleep staging 44,46,53,55,57,58 and sleep position.…”
Section: Nasal Cycle and The Autonomic Nervous Systemmentioning
confidence: 99%
“…The nasal cycle is a normal ultradian physiological phenomenon that manifests in all mammals, 52 where each nasal airway takes turns at conducting a greater apportionment of tidal airflow. The status of airflow dominance between the right and left nasal airways is correlated with sympathetic and parasympathetic dominant states, respectively, as regulated by the ANS, 53,54 the lateralised ultradian rhythm of alternating cerebral hemispheric dominance 55,56 and is tightly coupled to sleep staging 44,46,53,55,57,58 and sleep position.…”
Section: Nasal Cycle and The Autonomic Nervous Systemmentioning
confidence: 99%
“…Normally, the airflow and resistance in each nasal airway alternates between a patent and partially congested state for periods ranging from 25 minutes to greater than 4 hours, with a mean of 2.5 hours [3][4][5]. Some evidence suggests that the nasal cycle is longer during sleep compared to the waking state [3,5,6]. During sleep, changes in the nasal cycle often coincide with postural changes and may occur more often in transitions to REM sleep [5][6][7].…”
Section: Nasal Cyclementioning
confidence: 99%
“…At rest, in a normal individual uninostril dominance is seen, characterized by alternating patency of right and left nostrils in a 24 hour cycle. 1 Alterations in nasal cycle periodicity have been linked to various diseases. It has been reported that regular practice of breathing exercises are known to alter autonomic function and that Right Nostril Breathing (RNB) technique stimulates sympathetic activity by activating left cerebral hemisphere and Left Nostril Breathing (LNB) stimulates parasympathetic activity by activating right cerebral hemisphere.…”
Section: Introductionmentioning
confidence: 99%